מִתְהַלֵּךְ: Was Yahweh Walking in the Garden?— A New Solar Interpretation of Genesis 3:8 - Sarlo, Daniel (Antiguo Oriente, 2024)
The notion that Yahweh was walking in the Garden of Eden in search of Adam and Eve has endured since the first English translation of the Hebrew Bible. Indeed, most modern English Bibles render מִתְהַלֵּךְ in Gen 3:8 as “walking.” However, the verb הלך simply means “to go, travel” and is applied to a wide variety of animate and inanimate subjects in the Hebrew Bible. Not only does the specificity of the translation “walking” exhibit unnecessary bias, reinforcing the notion that Yahweh was an anthropomorphic god who travelled the earth on foot, it conflicts with Yahweh’s usual method of travel in the Hebrew Bible.